2019
DOI: 10.1017/s0007114518003185
|View full text |Cite
|
Sign up to set email alerts
|

The elongation of very long-chain fatty acid 6 gene product catalyses elongation ofn-13 : 0 andn-15 : 0 odd-chain SFA in human cells

Abstract: Normal odd-chain SFA (OCSFA), particularly tridecanoic acid (n-13 : 0), pentadecanoic acid (n-15 : 0) and heptadecanoic acid (n-17 : 0), are normal components of dairy products, beef and seafood. The ratio of n-15 : 0:n-17 : 0 in ruminant foods (dairy products and beef) is 2:1, while in seafood and human tissues it is 1:2, and their appearance in plasma is often used as a marker for ruminant fat intake. Human elongases encoded by elongation of very long-chain fatty acid (ELOVL)1, ELOVL3, ELOVL6 and ELOVL7 cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 65 publications
5
11
0
Order By: Relevance
“…ELOVL6 is known to catalyze elongations of n‐SFA with 12, 14, and 16 carbons . Our recent study also showed ELOVL6 activity toward odd chain n‐SFA with 13 and 15 carbons . Here, we found ELOVL6 substrate specificity to BCFA anteiso ‐15:0, thus ELOVL6 has substrate specificity to both n‐SFA and BCFA with 12–16 carbons.…”
Section: Discussionsupporting
confidence: 73%
“…ELOVL6 is known to catalyze elongations of n‐SFA with 12, 14, and 16 carbons . Our recent study also showed ELOVL6 activity toward odd chain n‐SFA with 13 and 15 carbons . Here, we found ELOVL6 substrate specificity to BCFA anteiso ‐15:0, thus ELOVL6 has substrate specificity to both n‐SFA and BCFA with 12–16 carbons.…”
Section: Discussionsupporting
confidence: 73%
“…Multiple studies have demonstrated that dietary C15:0 intake and associated circulating concentrations are linearly correlated 32,57,71 . This supports that, although C15:0 can be elongated from propionate or C13:0, there does not appear to be strong endogenous, de novo production of C15:0 58,72 . In addition to linear correlations between dietary and circulating C15:0 concentrations, evidence of C15:0 as a primarily exogenous fatty acid includes lack of peroxisomal 2-hydroxyacyl-CoA lyase and liver-based α-oxidation involvement in endogenous production of C15:0, lack of strong correlations between orally administered propionate with plasma C15:0 concentrations, and no evidence of effects of changing gut microbiota on circulating C15:0 57,72,73 .…”
Section: Essential Fatty Acid Criterium Evidence Referencessupporting
confidence: 67%
“…Further, our studies demonstrate that ingestion of C15:0 alone increases both C15:0 and C17:0 plasma concentrations in vivo, suggesting that ingestion of C15:0 may offer benefits of both raised circulating C15:0 and C17:0, including improved glucose control. Elongation of C15:0 to C17:0 has been demonstrated in MCF7 human cells transfected with human elongases encoded by elongation of very long-chain fatty acid 6 (ELOVL6), as well as ELOVL7, providing a feasible mechanism for increased C17:0 concentrations following C15:0 ingestion 58 .…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with an increase in BAT NEFA oxidation as a response to cold-induced thermogenesis [ 43 , 44 ]. The observation of significant cold-induced concentration changes in most odd-chain NEFA is also of interest given the evolving understanding of odd-chain lipid synthesis and metabolism in humans [ 45 , 46 ]. Previously thought to be strictly prokaryote-derived, it is now recognized that odd-chain fatty acids can be obtained through diet [ 47 ], produced by intestinal microbiota activity [ 48 ], endogenously synthesized from propionic acid, alpha–oxidation of hydroxylated fatty acids or produced from branched chain amino acids [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%